Building a bridge between the syntax and semantics of UML collaborations - Cibrán, María Agustina; Mola, Vanesa; Pons, Claudia Fabiana; Russo, Wanda Mariana (2000)
The specification of the UML in general, and the specification of Collaboration Diagrams in particular, is semi-formal. This lack of precise semantics can lead to several problems such us different interpretations, ambiguities, etc. In this paper, we propose a formalization of the syntax and semantics of Collaboration diagrams in the formal specification language Object-Z. A collaboration diagram may be presented at two different levels: specification level (syntax) or instance level (semantics). In our formalization we take into account both levels of abstraction. Moreover, we provide a function (sem) that maps a Collaboration into its semantic domain. During this formalization process, we discovered inconsistencies and ambiguities, which motivated the discussion of some improvement ideas that will be presented in this document.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
European Conference on Object-Oriented Programming (14ta : 2000 jun. 12-16 : Sophia Antipolis; Cannes)
Keywords: UML